2020
DOI: 10.3390/atmos11050482
|View full text |Cite
|
Sign up to set email alerts
|

Fine and Coarse Carbonaceous Aerosol in Houston, TX, during DISCOVER-AQ

Abstract: To investigate major sources and trends of particulate pollution in Houston, total suspended particulate (TSP) and fine particulate matter (PM2.5) samples were collected and analyzed. Characterization of organic (OC) and elemental (EC) carbon combined with realtime black carbon (BC) concentration provided insight into the temporal trends of PM2.5 and coarse PM (subtraction of PM2.5 from TSP) during the Deriving Information on Surface Conditions from Column and VERtically Resolved Observations Relevant to Air Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Lower concentration of both PM and CA are usually measured in urban and rural sites of USA (e.g. [24,25]) and Europe (e.g. [26,27]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower concentration of both PM and CA are usually measured in urban and rural sites of USA (e.g. [24,25]) and Europe (e.g. [26,27]).…”
Section: Introductionmentioning
confidence: 99%
“…Fig 24. Apportionment of the absorption coefficient b abs obtained wintertime at a rural site in the Italian Apennines at λ = 375 nm (UV).The raw value of the absorption Angstrom is also shown on the right axis.…”
mentioning
confidence: 99%
“…The abundance of soot particle sources and the high levels of photochemical activity in Houston make it an ideal location for studying urban soot aerosol characteristics and atmospheric processing. Previous ambient measurements in Houston have reported average BC concentrations ranging between 0.31 and 0.80 µg m -3 (Levy et al, 2013;Yoon et al, 2020). Additionally, a study utilizing ambient vapors within an environmental chamber in Houston found that after 18 hours of atmospheric processing, monodisperse BC aerosol is transformed from a highly fractal morphology into spherical particles with a significant simultaneous increase in absorption enhancement (Eabs) (Peng et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This study is part of the DOE Sponsored TRacking Aerosol Convection Interactions Experiment (TRACER), which aims to unravel the interactions between clouds and aerosols in urban areas. Houston is a subtropical city heavily impacted by anthropogenic emissions from gasoline and diesel vehicles, cargo ships, and petrochemical industries (Al-Naiema et al, 2018;Bean et al, 2016;Schulze et al, 2018;Yoon et al, 2020). The abundance of soot particle sources and the high levels of photochemical activity in Houston make it an ideal location for studying urban soot aerosol characteristics and atmospheric processing.…”
Section: Introductionmentioning
confidence: 99%
“…The Gulf Coast Aerosol Research and Characterization Study (GC-ARCH), a companion study to TexAQS, focused on investigating the chemical composition and sources of PM and understanding its formation and transformation in southeastern Texas . The Second Texas Air Quality Study (TexAQS II) conducted during 2005 and 2006 included an intensive field campaign, TexAQS 2006/Gulf of Mexico Atmospheric Composition and Climate Study (GoMACCS), and provided insights into the factors that control the formation and transport of air pollutants in southeastern Texas. The 2013 Deriving Information on Surface Conditions from Column and Vertically Resolved Observations Relevant to Air Quality (DISCOVER-AQ) campaign further characterized the spatial variations of PM sources and chemistry in the greater Houston area. Many recent smaller-scale field campaigns in Texas also have added to our understanding of aerosol sources in the region. However, these studies have all centered in Eastern Texas, primarily in the large urban centers of Houston–Galveston–Brazoria and Dallas–Fort Worth, and have focused on the impact of local urban, industrial, and biogenic emissions sources.…”
Section: Introductionmentioning
confidence: 99%